7Ps theory of service marketing innovation: a survival strategy for hotel sector post Covid-19 in China / Yang Peng and Watsida Boonyanmethaporn - Peng, Yang; Boonyanmethaporn, Watsida (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Significant impact of COVID-19; reducing demand from hotels, shifting customer needs, and increasing costs of prevention, have all intensified competition in the hotel industry. China, as one of the best countries in the world in terms of COVID-19 prevention and control, has taken the lead in the post-COVID-19 era. The service marketing strategy has become a key element in the full range of corporate services to seize the opportunities by enhancing the culture of corporate personnel, personalization of products and construction of environmental facilities. This paper examines the current marketing situation and problems in the hotel industry by conducting a SWOT analysis, PEST analysis and local market segmentation analysis using China as an example. It then applies the 7P theory of service marketing to make recommendations from seven aspects: product, price, channel, promotion, personnel management, tangible display and service process. The 7PS practices are of great practical importance to the long-term development of enterprises and helps hotel brands to develop better. Guiding enterprises to explore its application on a theoretical basis, while testing its effects would be good for further research.